THINKING ABOUT COMPUTER SYSTEMS TO SUPPORT DESIGN SYNTHESIS. - Vidal, Rosario; Mulet, Elena (Communications of the ACM, 2006)
This article focuses on enabling computer-aided design systems (CAD) with the ability to automatically invent new solutions. This idea is controversial because some researchers believe creativity is too unpredictable to be envisaged by a computer system, while others defend the potential capacity of computers to reach novel solutions using mechanisms very different from those humans use to be creative. The authors argue that several problems must be solved before a system can be developed that is significantly more helpful than current CAD systems, and point out that no autonomous design system that offers the same degree of satisfaction as working with a human designer has yet been developed.